High‐Performance All‐Small‐Molecule Organic Solar Cells Enabled by Regio‐Isomerization of Noncovalently Conformational Locks. (4th February 2022) - Zhang, Xin; Qin, Linqing; Li, Yuhao; Yu, Jianwei; Chen, Hao; Gu, Xiaobin; Wei, Yanan; Lu, Xinhui; Gao, Feng; Huang, Hui
Abstract: The power conversion efficiencies (PCEs) of organic solar cells (OSCs) have surpassed 19% thanks to the innovation of polymer donors and molecular acceptors. However, the batch‐to‐batch variations in polymer materials are detrimental to the reproducibility of the device performance. In comparison, small‐molecule donors (SMDs) possess some unique advantages, such as well‐defined molecular weights, easy purification, and excellent batch‐to‐batch repeatability. Herein, a pair of regioisomeric SMDs (BT‐O1 and BT‐O2 ) has been synthesized with alkoxy groups as S···O noncovalently conformational locks (NoCLs) at the inner and outer position, respectively. Theoretical and experimental results reveal that the regioisomeric effect has a significant influence on the light‐harvest ability, energy levels, molecular geometries, internal reorganization energy, and packing behaviors for the two SMDs. As a result, BT‐O2 ‐based binary device shows an impressive PCE of 13.99%, much higher than that of BT‐O1 based one (4.07%), due to the better‐aligned energy level, more balanced charge transport, less charge recombination, lower energy loss, and more favorable phase separation. Furthermore, the fullerene derivative PC71 BM is introduced into BT‐O2 :H3 as the third component to achieve a notable PCE of 15.34% (certified 14.6%). Overall, this work reveals that NoCLs is a promising strategy to achieve high‐performance SMDs for all‐small‐molecule OSCs. Abstract : All‐small‐molecule organic solar cells (ASM‐OSCs) have received a lot of attention owing to several advantages such as well‐defined molecular weights, easy purification, and satisfactory batch‐to‐batch repeatability. Herein, two isomeric small‐molecule donors (SMDs) containing S···O noncovalently conformational locks (NoCLs) are reported. Upon regio‐isomerization of NoCLs, high power conversion efficiencies of 13.99% and 15.34% are achieved for binary and ternary ASM‐OSCs.